A comparative study of γ-ray spectrometers in various applications - Barlas, Alexandros; Siltzovalis , Giwrgos; Balodima, Paraskevi; Mertzimekis, Theo J.; Madesis, Ioannis; Lagaki, Varvara (HNPS Advances in Nuclear Physics, 2024)
The present work concentrates on the detailed study of various types of γ-radiation spectrometers used mainly for applications. More specifically, various experiments were carried out to characterize and compare two (2) different high-purity germanium (HPGe) detectors, one (1) NaI scintillation detector, three (3) CdZnTe (CZT) detectors with standard calibration sources (152Eu, 137Cs and 22Na). In the context of the present work, the main focus was on the efficiency and the energy resolution of the detectors, but also on the angular response and operation of the CZT.